INDUSTRI BATUBARA DARI SISI EKONOMI, POLITIK, DAN LINGKUNGAN - Garcia Krisnando Nathanael (PARAPOLITIKA: Journal of Politics and Democracy Studies, 2021)
Coal is a crucial source of energy for Indonesia as a power plant. Abundant national coal reserves make Indonesia one of the largest coal producers in the world. Coal is the most potential natural resource commodity for Indonesia because it is able to provide a large contribution to the country's economy. With great potential, the Indonesian government then regulates business practices in the domestic coal sector so that its implementation is in accordance with regulations. This article is written to understand the coal industry from an economic, political and environmental perspective. The article is written using qualitative methods by collecting data from literature studies and online searches. Research shows that the coal industry in Indonesia has an impact on the economy, politics and the environment in Indonesia.